2016
DOI: 10.1038/nrclinonc.2016.108
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive metabolic imaging of brain tumours in the era of precision medicine

Abstract: The genomic revolution in cancer has uncovered a variety of mutations in primary brain tumors. This has created an urgent need to develop non-invasive imaging biomarkers to assess and integrate this genetic information in the clinical management of patients. Metabolic reprogramming is a central hallmark of cancers including brain tumors. Many of the molecular pathways implicated in brain tumors directly reprogram metabolism. This provides the opportunity to devise in vivo metabolism-based imaging modalities fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 175 publications
0
64
0
Order By: Relevance
“…For orthotopic tumor model (Figure ), noninvasive clear pinpointing deep brain tumor through skull and scalp is of significant importance for image guided surgery and therapy . Before systematic injection of P1 NPs and P1 RGD NPs, bioluminescence imaging showed that glioma cells labeled with luciferase were highly bioactive (Figure b), while magnetic resonance imaging results revealed the location of tumor beneath skull at a depth of 3 mm with confirmed tumor size (Figure c).…”
mentioning
confidence: 99%
“…For orthotopic tumor model (Figure ), noninvasive clear pinpointing deep brain tumor through skull and scalp is of significant importance for image guided surgery and therapy . Before systematic injection of P1 NPs and P1 RGD NPs, bioluminescence imaging showed that glioma cells labeled with luciferase were highly bioactive (Figure b), while magnetic resonance imaging results revealed the location of tumor beneath skull at a depth of 3 mm with confirmed tumor size (Figure c).…”
mentioning
confidence: 99%
“…[5][6][7][8][9][14][15][16][17] As the quantitative measurements derived from DWI (eg, mean diffusivity) and DCE (eg, volume transfer constant) are utilized in clinical trials of new treatment strategies, or for precision medicine and personalized cancer care, the technical confidence of these measurements in repeatability and reproducibility is ever more critical. [18][19][20] Expert task forces of the Quantitative Imaging Biomarkers Alliance (QIBA) have devoted significant resources to write DWI and DCE profiles and review over 1000 scientific articles in this area, but such literature review efforts have yielded few original articles with adequately described testretest data. The lack of repeatability and reproducibility literature in this area creates a roadblock for clinical translation of quantitative DWI and DCE-MRI.…”
mentioning
confidence: 99%
“…Analyses of patient-derived tumor organoids, for example, could include predictive modeling and experimental validation for development of treatment strategies, both initially and with recurrence [235237]. The influence of Warburg status could also be integrated into such personalized models if monitoring its influence on responsiveness of cancer to chemotherapy proves useful for selectively killing tumors [238]. Moreover, yeast phenomic models could be tailored to individual patients to examine more complex interactions: for example, in the background of homologous recombination deficiency [145].…”
Section: Discussionmentioning
confidence: 99%